2018
DOI: 10.4000/formationemploi.5368
|View full text |Cite
|
Sign up to set email alerts
|

La transmisión profesional en situación de trabajo : un enfoque ergonómico

Abstract: n La transmission professionnelle en situation de travail : une approche ergonomique La réflexion sur la transmission occupe une large place au sein de nombreuses disciplines. Nous l'aborderons ici sous l'angle d'une approche ergonomique, en mobilisant une recherche menée auprès de personnels soignants. Nous montrons que la transmission professionnelle constitue une activité à part entière, qui doit faire sa place dans l'activité de travail. Dès lors, nous insistons, d'une part, sur la diversité et la variabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
5
0
5
Order By: Relevance
“…With the additional records analyzed within the disciplines under the scope of Theory of Activity Research and social sciences (e.g., Work Psychology, Ergonomics), real work activity should be valued and transmission should take place as part of work activity. It can be achieved through action situations that are interpreted by workers, taking into account their life and work experience (e.g., Cloutier et al, 2012 ), maintaining a variable and evolutionary nature reconfigured according to the circumstances (Thébault, 2018 ). This last aspect is essential, since we have found that some practices implemented in the studies (e.g., static digital platforms; documents) do not contemplate the possibility of revisiting and updating the available contents, thus putting them at risk of becoming obsolete and of little use for learning and work performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the additional records analyzed within the disciplines under the scope of Theory of Activity Research and social sciences (e.g., Work Psychology, Ergonomics), real work activity should be valued and transmission should take place as part of work activity. It can be achieved through action situations that are interpreted by workers, taking into account their life and work experience (e.g., Cloutier et al, 2012 ), maintaining a variable and evolutionary nature reconfigured according to the circumstances (Thébault, 2018 ). This last aspect is essential, since we have found that some practices implemented in the studies (e.g., static digital platforms; documents) do not contemplate the possibility of revisiting and updating the available contents, thus putting them at risk of becoming obsolete and of little use for learning and work performance.…”
Section: Discussionmentioning
confidence: 99%
“…between two or more people, in a given situation (Thébault, 2018) and implies the manifestation of the experience and its transformation into a dynamic process of action and coconstructed learning-for the newcomers and the experienced workers (Gaudart and Thébault, 2012). It is then perceived that the transmission can occur informally (on a daily basis, without support from HR teams) or via knowledge management mechanisms (Cloutier et al, 2012).…”
Section: Introduction Managing Knowledge In Professional Contextsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elle implique une appréhension et une analyse diachronique de l'activité, des parcours professionnels Enjeux d'autonomie pour la transmission des savoirs et savoir-faire des trava... dans une perspective de construction des compétences, de l'expérience et de la santé (Delgoulet & Vidal-Gomel, 2013 ;Hélardot, Gaudart, & Volkoff, 2019 ;Molinié, Gaudart, & Pueyo, 2012 ;Reboul, Delgoulet, Gaudart, & Sutter, 2020). Ces travaux ont permis de « mettre à distance des idées reçues » (Thébault, 2016) en soulignant la complexité du processus de transmission et la diversité des situations et des personnes qu'il implique. La transmission peut se construire dans une dynamique de relation en binôme (noviceexpérimenté), ou au sein de collectifs de travail, de préférence stables, en fonction des possibilités effectives des travailleurs face aux contraintes et exigences du travail quotidien (e.g.…”
Section: La Transmission Des Savoirs Et Du Savoir-faire Au Travailunclassified
“…La transmission peut se construire dans une dynamique de relation en binôme (noviceexpérimenté), ou au sein de collectifs de travail, de préférence stables, en fonction des possibilités effectives des travailleurs face aux contraintes et exigences du travail quotidien (e.g. Cloutier et al, 2012 ;Thébault, 2018).…”
Section: La Transmission Des Savoirs Et Du Savoir-faire Au Travailunclassified